Aquarium fish - Mills, Dick.; Young Jerry (Boston : Distribution by Houghton Mifflin Co., 1993)
Provides photographs and descriptive information on more than 500 marine and freshwater fish varieties.
Includes index.
Library Journal.
Wilson's Public Library.
Wilson's Senior High School.
Adult
Keywords: Aquarium fishes -- Identification; Aquarium fishes -- Pictorial works; Aquariums -- Identification; Aquariums -- Pictorial works; Fishes -- Identification; Fishes -- Pictorial works